2021
DOI: 10.1088/1755-1315/890/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of spiny lobster, Panulirus homarus fed fresh food and formulated diet

Abstract: To date, lobster aquaculture relies on fresh food for feeding; however, the availability of fresh food is limited and its excessive use causes environmental degradation. Therefore, formulated diet is required to establish sustainable lobster aquaculture. Concerning this issue, this study was carried out to assess the growth and survival of spiny lobster Panulirus homarus fed fresh food and formulated diet. The study was conducted in a completely randomized design (CRD) with 3 groups of treatments and 3 replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Previous research shows that lobster growth was obtained from lobsters fed a combination of pellets and fresh food. This was probably caused by the better nutrient balance in the combination of pellet and fresh food, which supported better lobster growth [22]. This experiment results indicated various studies of lobster feed are needed to develop lobster feed, especially to formulate palatable and high-performance dry pellets to support lobster grow-out [9].…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous research shows that lobster growth was obtained from lobsters fed a combination of pellets and fresh food. This was probably caused by the better nutrient balance in the combination of pellet and fresh food, which supported better lobster growth [22]. This experiment results indicated various studies of lobster feed are needed to develop lobster feed, especially to formulate palatable and high-performance dry pellets to support lobster grow-out [9].…”
Section: Resultsmentioning
confidence: 74%
“…The high lipid values were contributed by fish meal, fresh fish, fresh mussels, fresh crab, and fish oil. Fish, shrimp, and small mussels indicated a relatively high content of lipids [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lobsters are known as a valuable crustacean that has high economical value in the market. The demand of lobsters are high not only in domestic, but also in international market [1]. To fulfil the demand of the market, lobster supply still depend on capturing activities.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of fresh and artificial feed for grow-out of lobster had been experimented in controlled tanks [1]. The result of this experiment showed that the combination of fresh food and formulated diet gave better growth performance, but the survival rate was better when the lobster were fed formulated diet.…”
Section: Introductionmentioning
confidence: 99%